2014
DOI: 10.1111/aogs.12388
|View full text |Cite
|
Sign up to set email alerts
|

Maternal blood pressure and heart rate response to pelvic floor muscle training during pregnancy

Abstract: Pelvic floor muscle training in nulliparous sedentary pregnant women does not increase BP. It significantly increases HR during the exercise sessions, but only for a limited period of time and with no negative long-term effect on BP or HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Due to this homogeneity, we believe that the results mentioned were achieved by the proposed training. An important and well‐designed study by Ferreira et al 2015 found a change in HR during the PFMT in pregnant women, reaching 70% of the calculated maximum HR, although the BP (systolic and diastolic) did not change after each training session 7 . This shows that although it is a small muscle group, there is some effort to perform the maximum contraction, even without the use of external loads.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Due to this homogeneity, we believe that the results mentioned were achieved by the proposed training. An important and well‐designed study by Ferreira et al 2015 found a change in HR during the PFMT in pregnant women, reaching 70% of the calculated maximum HR, although the BP (systolic and diastolic) did not change after each training session 7 . This shows that although it is a small muscle group, there is some effort to perform the maximum contraction, even without the use of external loads.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding PFMT, no studies were found evaluating the response of cardiovascular autonomic modulation variables both in pregnancy and in other populations, just in heart rate and blood pressure. 7 However, even lowintensity (walking) aerobic training could attenuate the decreased parasympathetic modulation and also prevented increased SAP during pregnancy, showing that the low intensity may also be effective in this population, although it is another type of exercise. 34 Still, even the contraction of small muscle groups or low-intensity exercise are sufficient to raise BP and HR, and these values increased significantly when these exercises are accompanied by the Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, pelvic floor muscle contraction is most likely a combination of a concentric and isometric contractions [15,16]. Many studies in the literature have indicated the use of maximum voluntary contractions of the pelvic floor muscle to obtain training benefits [6,14].…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that exercise generates resistance to blood flow in the uterine circulation. In a recent longitudinal study involving 27 healthy, nulliparous, pregnant women, Ferreira et al 62 examined whether maternal heart rate and BP changed in response to pelvic floor muscle training during pregnancy. Systolic and diastolic BP were measured before and after each training session and maternal heart rate was measured during each session.…”
Section: Exercise and Pregnancymentioning
confidence: 99%